Adherence and Viral Suppression Among Participants of the Patient-centered Human Immunodeficiency Virus (HIV) Care Model Project: A Collaboration Between Community-based Pharmacists and HIV Clinical Providers. (6th April 2019) - Byrd, Kathy K; Hou, John G; Bush, Tim; Hazen, Ron; Kirkham, Heather; Delpino, Ambrose; Weidle, Paul J; Shankle, Michael D; Camp, Nasima M; Suzuki, Sumihiro; Clay, Patrick G; ,
Abstract: Background: Human immunodeficiency virus (HIV) viral suppression (VS) decreases morbidity, mortality, and transmission risk. Methods: The Patient-centered HIV Care Model integrated community-based pharmacists with HIV medical providers and required them to share patient clinical information, identify therapy-related problems, and develop therapy-related action plans. Proportions adherent to antiretroviral therapy (proportion of days covered [PDC] ≥90%) and virally suppressed (HIV RNA <200 copies/mL), before and after model implementation, were compared. Factors associated with postimplementation VS were determined using multivariable logistic regression; participant demographics, baseline viral load, and PDC were explanatory variables. PDC was modified to account for time to last viral load in the year postimplementation, and stratified as <50%, 50% to <80%, 80% to <90%, and ≥90%. Results: The 765 enrolled participants were 43% non-Hispanic black, 73% male, with a median age of 48 years; 421 and 649 were included in the adherence and VS analyses, respectively. Overall, proportions adherent to therapy remained unchanged. However, VS improved a relative 15% (75% to 86%, P < .001). Higher PDC (adjusted odds ratio [AOR], 1.74 per 1-level increase in PDC category [95% confidence interval CI, 1.30–2.34]) and baseline VS (AOR, 7.69 [95% CI, 3.96–15.7]) were associated with postimplementation VS. Although non-Hispanic black persons (AOR, 0.29 [95% CI, .12–.62]) had lower odds of suppression, VS improved a relative 23% (63% to 78%, P < .001). Conclusions: Integrated care models between community-based pharmacists and primary medical providers may identify and address HIV therapy–related problems and improve VS among persons with HIV. Abstract : Although adherence to antiretroviral therapy remained unchanged, before and after Patient-centered Human Immunodeficiency Virus (HIV) Care Model implementation, viral suppression improved 15%. In addition, there was a notable improvement (23% increase) in viral suppression among non-Hispanic black persons.